2021
DOI: 10.1080/14756366.2021.1988945
|View full text |Cite
|
Sign up to set email alerts
|

Dithiocarbamates effectively inhibit the α-carbonic anhydrase from Neisseria gonorrhoeae

Abstract: Recently, inorganic anions and sulphonamides, two of the main classes of zinc-binding carbonic anhydrase inhibitors (CAIs), were investigated for inhibition of the α-class carbonic anhydrase (CA, EC 4.2.1.1) from Neisseria gonorrhoeae , NgCA. As an extension to our previous studies, we report that dithiocarbamates (DTCs) derived from primary or secondary amines constitute a class of efficient inhibitors of NgCA. K I s ranging between 83.7 and 827 nM were measured f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Finally, dithiocarbamates, coumarins, and carboxylic acids inhibited bacterial CAs through a distinct mode of interaction. [ 25,26 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, dithiocarbamates, coumarins, and carboxylic acids inhibited bacterial CAs through a distinct mode of interaction. [ 25,26 ]…”
Section: Introductionmentioning
confidence: 99%
“…Finally, dithiocarbamates, coumarins, and carboxylic acids inhibited bacterial CAs through a distinct mode of interaction. [25,26] In our previous study, we have reported a computational approach to identify VchCA inhibitors culminating in the discovery of N-(4sulfamoylbenzyl)biphenyl-4-carboxamide (Figure 1, compound 4) as a small molecule capable of reducing CA activity of all three classes expressed in V. cholerae in the nanomolar range in stopped-flow hydrase assay [22] and marked selectivity over hCA I/hCA II isoforms. To collect information about its binding mode, we have also described its hypothetical orientation into the VchCAβ cavity through docking simulations (Figure 2).…”
mentioning
confidence: 99%
“…Since the DTCs investigated earlier 20 showed an intermediate behaviour between the ineffective MTCs and the quite effective sulphonamides 15 , 16 , we can speculate that the highly hydrophilic nature of the MTCs may interfere with their uptake by the bacterial cells. Thus, effective compounds targeting bacterial CAs should not only be lipophilic enough to cross the bacterial cell wall or traverse the water-filled porins, but also they should incorporate zinc-binding groups that allow a potent coordination to the active site metal ion, which is crucial both for catalysis and inhibition of these enzymes 27 .…”
Section: Resultsmentioning
confidence: 86%
“…Most such studies have been performed with sulphonamide CA inhibitors (CAIs), one of the most investigated class of inhibitors for these enzymes. However, other classes of CAIs have recently been investigated for their inhibitory potential against bacterial CAs, such as coumarins 19 , dithiocarbamates 20 and phenols 21 . Monothiocarbamates (MTCs) represent another class of zinc-binding CAIs 22 , which have not yet been investigated for their interaction with bacterial CAs.…”
Section: Introductionmentioning
confidence: 99%
“…The MICs of streptomycin, penicillin, ceftriaxone, tetracycline, doxycycline, azithromycin, and ciprofloxacin, in addition to zoliflodacin and gepotidacin (two compounds currently being evaluated in clinical trials for the treatment of gonorrhea) (Taylor, Morris, et al 2018;Taylor, Marrazzo, et al 2018), were determined against N. gonorrhoeae strains CDC-181, CDC-181-rpsLA128G, WHO-X, and WHO-X-rpsLA128G as well as FA 1090 (as a control) using the broth microdilution method as described previously (Alhashimi, Mayhoub, and Seleem 2019;Hewitt et al 2021;Naclerio et al 2021;Seong et al 2020;Giovannuzzi et al 2022). Briefly, a 1.0 McFarland bacterial solution was prepared and diluted in brucella broth supplemented with yeast extract, dextrose, proteose-peptone, NAD, pyridoxal, hematin, and IsoVitaleX to reach an inoculum of ~1×10 6 colony forming units (CFU)/mL.…”
Section: Determination Of the Minimum Inhibitory Concentrations (Mics...mentioning
confidence: 99%